Gender Role Characteristics and Entrepreneurial Self-Efficacy: A Comparative Study of Female and Male Entrepreneurs in China - Li, Chengyan; Bilimoria, Diana; Wang, Yelin; Guo, Xiaowei (Frontiers in Psychology, 2020)
This study, based on Bem’s (1974) gender schema theory, investigates gender differences in and the relationship between gender role characteristics and entrepreneurial self-efficacy (ESE) of 261 female and 265 male entrepreneurs in China. The results show that male and female entrepreneurs did not differ significantly in ESE or in masculine gender role characteristics, but differed significantly in feminine gender role characteristics. Examining four different stages in the entrepreneurial life cycle, we find that for female entrepreneurs, feminine characteristics had a positive influence on ESE in the searching and planning stages of entrepreneurship, and masculine characteristics had a positive influence on ESE in the searching stage. For male entrepreneurs, feminine characteristics had a positive influence on ESE in the searching and planning stages, and masculine characteristics had a positive influence on ESE in the marshalling and implementing stages. In addition, one feminine characteristic, “Friendly”, showed a positive association with male entrepreneurs’ ESE in the marshalling stage. Overall, the feminine gender role factor of “Friendly” and the masculine gender role factor of “Compete” played a greater role on ESE than other characteristics. Implications of the findings are discussed. This study contributes a new perspective to extant research on entrepreneurial self-efficacy and female entrepreneurship.